Functional demands and environmental factors: a geospatial analysis in users of primary health care (Research, Society and Development, 2022)
Objectives: to evaluate and analyze the association between functional demands and environmental factors of users of the primary health care (PHC). Methods: cross-sectional study that evaluated PHC users using the Problem Survey for Rehabilitation Protocol (PLPR) and the Inventory of Environmental Factors (CHIEF). Descriptive statistics, geo-spatial analysis and Multiple Linear Regression were applied for data analysis. Results: 230 users were evaluated and presented greater functional demand in the pain domains (mean=5.29; SD=3.55); energy and sleep (mean=3.17; SD=2.91); and mobility (mean=3.07; SD=2.51). The environmental factors that presented the most problems were 'services and assistance' (mean=0.66; SD=0.61) and 'physical structure' (mean=0.61; SD=0.65). The geo-spatial analysis identified that the regions covered by the basic health unit with the greatest presence of barriers corresponded to places of residence of users with more functional needs. Worse health perception (p=0.000), greater number of diagnosed diseases (p=0.000) and greater presence of barriers in 'services and assistance' (p=0.039) and 'physical structure' (p=0.000) were predictors of greater functional demand. The adjusted coefficient of the model was 43.2% (p=0.001). Final considerations: Users of primary health care have mild to moderate difficulties or deficiencies like pain, mobility and energy and sleep, which can be identified already in the embracement to the service. The most present environmental barriers in the evaluated territory were in 'services and assistance' and 'physical structure'. Better health perception, lower number of diagnosed diseases and lower presence of environmental barriers are predictors of greater functionality in PHC users.